Halichoerus grypus - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Halichoerus grypus (Fabricius, 1791). Skr. Nat. Selsk. Copenhagen, 1(2):167. TYPE LOCALITY: Listed by Scheffer (1958) as " Greenland ". DISTRIBUTION: Temperate and subarctic waters around Britain, Canada (Newfoundland area), Iceland, Greenland, Norway, Russia (Kola Peninsula), and Baltic Sea. SYNONYMS: atlantica Nehring, 1886; baltica Nehring, 1886; griseus Nilsson, 1820; halichoerus Thienemann, 1824; macrorhynchus Hornschuch and Schilling, 1851; pachyrhynchus Hornschuch and Schilling, 1851. Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on pages 329-330, DOI: 10.5281/zenodo.7359191